Starting Up A Home Cooking Meal Industry - Deva Kristianto Juwono, Aria; S. Gunawan, Benny (The Indonesian Journal of Business Administration, 2017)
Abstract - Tana Catering is a home catering industry innovation startup created by Miranti Wahjudi that serves good home cooking meals daily for busy women with a family to look after. A startup begins from an idea that should be able to offer new values that would attract a market by solving issues. A startup cannot be treated like an established company; it wouldn’t have the strong basis to implement the tools for a company. For startups, the Customer Development framework was developed by Steve Blank. This framework was designed to guide startups for more promising results. Tana Catering applied this framework in its development process. The framework consisted of searching a business model and executing it. The whole process will involve a lot of trial and error testing. This method will give fast factual information to guide the startup in making the right decisions. Tana Catering had developed a business model with the framework’s guide. It is now scaling up the market and standardizing activities to make it possible to evolve into a company. It had grown its subscribers to more than one thousand in less than eight months. This framework had assisted Tana Catering to find the right course without wasting to much precious resources. Keywords: startup, catering, home cooking, customer development